COMPUTER CONTROLLER SYSTEM VUI (Voice User Interface) BASE - Agus Ramdhani Nugraha (JUTEKIN (Jurnal Teknik Informatika), 2017)
In common operation system is physical component formations those are fitted-up in such a way face so can manage its own system or its outboard system. System controls is arrangement or operation process to one or many bigger (variable, parameter) so lies at one particular price range one particular. Systems other terminology control or tech conduct is tech arrangement, operation system, or controling system.In computer, human interaction with computer becomes thing that momentously, since concerns operation and optimise from that computer is alone to solve a period. That user and computer gets to interact so user feels to mark sense computer system sociability. Voice User Interface or ordinary abbreviated by VUI is One Of interface which be utilized alternatively communication among human and Computer that utilize voice media. Voice here being made as media gets interaction among man and operating system in going a computer. With this VUI'S method at expects communication among human and computer gets to more happen efficient.Keyword : Controller System, Computer, VUI ( Voice User Interface )